Gaya Hidup Urban dalam Perspektif Postmodern: Studi Etnografi Komunitas Gym terhadap Komunikasi dan Identitas - Razali, Geofakta; Puspita, Ratna (Jurnal Mahardika Adiwidia, 2023)
This research aims to analyze urban lifestyles in a postmodern context, with a focus on the Fitness First gym community in Senayan City, Jakarta. Through an ethnographic approach, this research explores how members of the gym community communicate and form their identities in urban spaces. Using ethnographic methods participant observation and in-depth interviews, this research identifies various aspects of communication that occur in interactions between community members, including symbols, body language, and the use of social media. The research results show that the gym community is not only a place to exercise but also a social space that influences the way individuals present themselves and interact in the broader context of urban society. These findings provide new insights into the relationship between urban lifestyle, communication, and identity formation in the postmodern era, especially in the context of urban gym communities in Jakarta.